Endothelial molecule levels (VCAM-1, ICAM-1) in uncomplicated malaria cases in Lagos, Nigeria - Uche T. Igbasi; Wellington A. Oyibo (Microbes, Infection and Chemotherapy)
Background. Elevated endothelial activation markers are linked to malaria syndromes due to the sequestration of Plasmodium falciparum-infected red blood cells in deep tissue vessels. This study evaluated vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) levels in uncomplicated malaria and their association with host factors. Methods. A cross-sectional study was conducted in four health facilities in Ikorodu, Lagos State, Nigeria. Blood samples from children and adults were screened for malaria via microscopy, and plasma ICAM-1 and VCAM-1 levels were measured using ELISA. Results. ICAM-1 (1.03 × 106 ± 20,689.2 pg/ml) and VCAM-1 (1.11 × 106 pg/ml; range: 3,725–6,273,725 pg/ml) levels were significantly higher in malaria-positive cases compared to controls (p < 0.01). The geometric mean parasite density was 11,183 parasites/μl, but ICAM-1 and VCAM-1 levels did not correlate with parasite density (p > 0.1). Packed cell volume (PCV) was significantly lower in malaria-positive cases (p = 0.042), with ICAM-1 and VCAM-1 negatively correlating with PCV (p < 0.05). Both markers were also inversely associated with age (p < 0.05). Conclusion. VCAM-1 and ICAM-1 levels are elevated in uncomplicated malaria, independent of parasite density but negatively associated with PCV and age, highlighting the role of endothelial activation in malaria pathology.